Central Venous Catheter Insertion: Advanced Clinical Techniques, Complication Prevention, and Evidence-Based Critical Care Practice - Al Nasser, Adel Nasser Mohammed; Nadia Saud Alatawi; Ayad Saper R. Alrawili; Helah Freah Alenazi; Fatimah Freih Alenezi; Najwan Fraih Alanazi; Alanood Faiiad Alriwaily; Abdullah Saeed Abdullah Moraya; Mohrah Hamoud Dughaylib Alrashdi; Refah Daifullah Alotaibi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Central Venous Catheters (CVCs) are indispensable devices in critical care, enabling advanced hemodynamic monitoring, administration of critical therapies, and provision of renal replacement. Their insertion, however, carries significant risks of mechanical, infectious, and thrombotic complications. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article provides a comprehensive review of modern CVC insertion, focusing on advanced techniques, complication prevention, and evidence-based best practices to optimize patient safety and procedural success in critical care settings. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A detailed narrative synthesis of current literature and clinical guidelines was conducted. The review examines anatomical considerations for common access sites (internal jugular, subclavian, femoral), evaluates the evidence for ultrasound-guided insertion, and analyzes strategies for preventing immediate and delayed complications. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Real-time ultrasound guidance is established as the standard of care, significantly improving first-attempt success and reducing mechanical complications like arterial puncture and pneumothorax. Site selection involves balancing risks: the internal jugular vein offers ease of ultrasound visualization; the subclavian vein has a lower infection risk but a higher pneumothorax risk; the femoral vein is useful in emergencies but carries higher thrombosis and infection risks. Strict adherence to maximal sterile barrier precautions and daily catheter care bundles are paramount for preventing catheter-related bloodstream infections. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Safe and effective CVC management requires a structured, multidisciplinary approach. Mastery of ultrasound-guided technique, meticulous aseptic practice, and vigilant post-procedural care by an interprofessional team are essential to minimize complications and maximize the therapeutic benefits of central venous access.